Postfeminism and Contemporary Hollywood Cinema - Gwynne, J.; Gwynne, J.; Muller, N.; Muller, N. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
By analyzing the negotiation of femininities and masculinities within contemporary Hollywood cinema, Postfeminism and Contemporary Hollywood Cinema presents diverse interrogations of popular cinema and illustrates the need for a renewed scholarly focus on contemporary film production.